Multi-omics resources for targeted agronomic improvement of pigmented rice - Sedeek, Khalid; Zuccolo, Andrea; Fornasiero, Alice; Weber, Annika M.; Sanikommu, Krishnaveni; Sampathkumar, Sangeetha; Rivera, Luis F.; Butt, Haroon; Mussurova, Saule; Alhabsi, Abdulrahman; Nurmansyah, Nurmansyah; Ryan, Elizabeth P.; et al. (Springer, 2023)
Pigmented rice (Oryza sativa L.) is a rich source of nutrients, but pigmented lines typically have long life cycles and limited productivity. Here we generated genome assemblies of 5 pigmented rice varieties and evaluated the genetic variation among 51 pigmented rice varieties by resequencing an additional 46 varieties. Phylogenetic analyses divided the pigmented varieties into four varietal groups: Geng-japonica, Xian-indica, circum-Aus and circum-Basmati. Metabolomics and ionomics profiling revealed that black rice varieties are rich in aromatic secondary metabolites. We established a regeneration and transformation system and used CRISPR–Cas9 to knock out three flowering time repressors (Hd2, Hd4 and Hd5) in the black Indonesian rice Cempo Ireng, resulting in an early maturing variety with shorter stature. Our study thus provides a multi-omics resource for understanding and improving Asian pigmented rice.